The Relationship Between Drug Information Services and the Level of Compliance in Hypertension Patients at Tuan Rondahaim Regional Hospital, Simalungun Regency in 2025 - Dosma Rosita Turnip; Evi Junita Sitorus; Norong Perangin-angin (Jurnal EduHealth, 2026)
Drug information services are very necessary, especially since many patients have not received adequate drug information about the drugs they are using, because incorrect use of drugs and non-compliance with taking drugs can harm patients. Patient compliance influences the success of treatment. Without patient awareness, therapy results will not be optimal, and this can even lead to treatment failure.Hypertension patients need to regularly check themselves at the hospital or independently at home periodically to monitor their condition and adjust their treatment in a timely manner for optimal healing effectiveness. Hypertension treatment aims to prevent and avoid dangerous complications. This study was descriptive with a prospective approach.In this study, the sampling technique used was nonprobability sampling with purposive sampling technique.The research instruments used were checklist sheets and questionnaires. The most respondents were in the 60-69 year age group, namely 44 respondents (44%), the most common gender classification for hypertension sufferers was female, namely 53 people (53%), the most common level of education was high school with a total of 55 people (55%), and the most common type of work was farmer with a total of 57 people (57%). Drug information services that are frequently provided are Drug Name, Dosage, How to Use and Indications, implemented 99% - 100%, Dosage Form (55%), Side effects (66%), Interactions 43%, and storage only 8%, while. Information that has not been provided is drug contraindications (0%) and drug stability (0%). The level of compliance is low with 58 respondents (58%), the level of compliance is high with 8 respondents (8%). Based on the results of the statistical test, there is a relationship using correlation, obtaining a significant value of 0.000, indicating that there is a relationship between drug information services and the level of compliance of hypertension patients